Structural and Non-Structural Assessment of Flood Control in Gunting River, Jombang Regency, East Java Province - Supriyono Supriyono (Journal of the Civil Engineering Forum, 2019)
Gunting River which is located in Jombang Regency of East Java Province, Indonesia encounters frequent flood event almost every year. It causes many problems in transportation, health, and economic activity. Thus, flood control which has been implemented in this area needs to evaluate. Design flood was analyzed using HEC-HMS 4.0 Software, while the hydraulic modeling used the unsteady flow simulation model by HEC-RAS 5.0.3 Software. The flood control simulation was conducted with 2 and 10-years return period. The simulation results with the normalization for 2-years (Q2) and 10-years return period (Q10) can effectively accommodate the exceed of flood discharge and lower the depth of runoff depth. The combination of normalization and embankment for can drain the maximum discharge up to 508.75 m3/s, and decrease run-off depth of 2.65 m. The land conservation of 17.8 km2 of the upper area in the watershed has lower the flood depth up to 0.16 m.